Sex represents a relevant interaction in Sprague–Dawley rats: the example of oesophageal length*. Issue 1 (1st January 2020) - Nuber, Maximilian; Lindner, Andreas; Baumgart, Jan; Baumgart, Nadine; Heimann, Axel; Schröder, Arne; Muensterer, Oliver J.; Oetzmann von Sochaczewski, Christina
ABSTRACT: Background: 8-week old Sprague Dawley rats represent the standard rodent model of oesophageal surgery, which is challenging and might be eased by larger oesophageal lengths. Therefore, we aimed to analyse whether oesophageal length would linearly increase with bodyweight and ensure comparable experimental conditions. Methods: We analysed 41 8-week old Sprague Dawley rats of both sexes by linear regression of oesophageal length with sex as an interaction term for bodyweight. Based on exploratory investigations, analyses were powered to 80% for a deviation of the regression's slope from zero. Results: Linear regression was statistically significant with F (3, 37) = 3.29, P =0.0312 with an adjusted R ² of 0.15 (95% CI: 0.02–0.43). Oesophageal length could be modelled by 4.56 (95% CI: 1.45–6.69) + 0.007 (95% CI: −0.002–0.019) x bodyweight in grams + 6.7 (95% CI: 1.86–11.1) x sex (1=male) – 0.02 (95% CI: −0.04–(−0.005)) x bodyweight x sex. Exploration of the interaction revealed that oesophageal length increased with bodyweight for female rats, but decreased in males. Conclusions: Sex represents a major interaction for oesophageal length in an age-adjusted cohort of Sprague Dawley rats. This may have relevant implications for reproducibility of rat models of oesophageal surgery, but may be different in inbred strains.